Efektifitas Hypnobirthing Terhadap Skala Nyeri Ibu Bersalin Inpartu Kala I Fase Aktif Di Wilayah Kerja Puskesmas Lebuh Dalem - Sihaloho, Rizka Yunita; Lathifah, Neneng Siti; Fitria, Fitria; Anggraini, Anggraini (MIDWIFERY JOURNAL, 2023)
Background : When the body is under stress, stress hormones, namely catecholamines and adrenaline will be released so that the body responds to fight and avoid. Practicing relaxation or using hypnobirthing techniques stimulates the emergence of endorphins at any time so that it can greatly assist the labor process in reducing pain during labor.Methods: This type of research is quantitative, the research design uses a pre-experimental design. Based on the presence or absence of treatment, this study used experimental research with One Group pretest-posttest research design. The number of samples in this study were 30 mothers who gave birth in the first stage of the active phase. The results of the bivariate analysis research can be concluded that the t-test results obtained p value 0.000 < (0.05) and CI-95% (0.738-1.727, 0.738-1.738) meaning that H0 is rejected and Ha is accepted, which means that there is an effect of hypnobirthing on the pain scale. for mothers in labor in the first stage of the active phase in the work areaConclusion: It is recommended for further researchers to be more in-depth and use different and more variables. Health workers can apply this hypnobirthing technique in handling childbirth in order to reduce the intensity of pain in childbirth and for the Midwifery DIV study program it can be an additional source and insight for readers about hypnobirthing techniques. Keywords: hypnobirthing, pain, kala I ABSTRAK  Latar Belakang : Saat tubuh dalam keadaan stres, hormon stres yaitu katekolamin dan adrenalin akan dilepaskan sehingga tubuh memberikan respons untuk melawan dan menghindar. Berlatih relaksasi atau penggunaan teknik hypnobirthing memacu munculnya endofrin setiap saat sehingga dapat sangat membantu proses persalinan dalam mengurangi rasa nyeri pada proses persalinan.Metode : Jenis penelitian ini adalah kuantitatif,  Rancangan penelitian menggunakan pre-experimental design. Berdasarkan ada tidaknya perlakuan penelitian ini menggunakan penelitian ekperimental dengan desain penelitian One Group pretest-posttest. Jumlah sampel pada penelitian ini adalah sebanyak 30 orang ibu bersalin kala I fase aktif. Hasil penelitian analisa bivariat dapat disimpulkan  hasil uji t didapat p value 0,000< α (0,05) dan nilai CI-95% (0,738-1.727, 0,738-1.738) artinya H0 ditolak dan Ha diterima, yang berarti ada pengaruh hypnobirthing terhadap skala nyeri pada ibu bersalin inpartu kala I fase aktif di wilayah kerjaKesimpulan : Disarankan kepada peneliti selanjutnya agar lebih mendalam dan menggunakan variabel yang berbeda dan lebih banyak lagi. Kepada tenaga kesehatan dapat menerapkan teknik hypnobirthing ini dalam penanganan persalinan agar mengurangi intensitas nyeri pada ibu bersalin dan untuk prodi DIV Kebidanan dapat menjadi sumber tambahan dan wawasan bagi pembaca mengenai teknik hypnobirthing. Kata Kunci : hypnobirthing, nyeri, kala I